Penerapan Metode Demonstrasi untuk Meningkatkan Hasil Belajar Fisika Siswa - Ramlah Saleh (Jurnal Kreatif Online, 2021)
This study aimed to determine the improvement of student learning outcomes in class 10th TKR A SMKN 3 Palu by applying the demonstration method in physics subjects. The type of research used was classroom action research (CAR) with 2 cycles each through the stages of planning, implementation, observation and reflection. The subjects in this research were 10th grade of TKR A students at SMKN 3 Palu in the 2019/2020 academic year. Data related to the value of learning outcomes of each student in each cycle were analyzed descriptively by looking for the average value which was then followed by determining the value of student completeness, classical completeness value, and increasing student learning outcomes. The indicator of success in this study was if classical completeness ≥ 80. The results of the research in the first cycle showed that the highest score was 80, the lowest score was 45. The average score of students in the first cycle was 64.2 with 18 students who completed learning. Then the percentage of classical completeness was 53%. In the second cycle, the highest score was 95, the lowest score was 70. The average score of students in the second cycle was 78.5 with 29 students who completed learning. Then the classical completeness is 85.3%. Based on the increase in the percentage of student learning completeness of class 10th TKR A SMKN 3 Palu for the 2019/2020 academic year, the application of the demonstration method can improve physics learning outcomes.